The three musketeers - Dumas, Alexandre
During the reign of France's King Louis XIV, D'Artagnan and three musketeers unite to defend the honor of Anne of Austria against the plots of Cardinal Richeliu.
Keywords: Fiction. -- History -- France; FICTION -- General